The Analysis of E-System Effectiveness to Increase Individual Taxpayer Compliance in Submitting Annual Returns - Parintak, Ulvy Restiana; Awaluddin, Ishak; Tamburaka, Sulvariany; Hadisantoso, Erwin (Journal of International Conference Proceedings, 2024)
This study aims to determine the effectiveness and role of the electronic taxation system in enhancing taxpayer compliance. Data collection methods in this study included questionnaires, interviews, and documentation, analyzed using descriptive techniques. The results showed that the efficiency of the electronic taxation system, particularly in the form of e-SPT within the Kendari General Tax Administration, was classified as effective in 2020. This indicates that the e-SPT application was implemented effectively, simplifying the process for taxpayers to complete their annual tax returns (SPT) electronically. Similarly, the effectiveness of the electronic system in the form of an electronic archive in 2020 was classified as very effective. This signifies that electronic media are highly beneficial for taxpayers in reporting SPT, as the system operates online and in real-time. Additionally, the number of SPT reports increased significantly with the availability of an electronic archive compared to the manual reporting system. Consequently, the improved efficiency of the electronic taxation system was strongly correlated with a higher level of taxpayer compliance, as taxpayers fulfilled their tax obligations to the maximum.Keywords: Compliance; e-Filing; e-SPT; Personal Taxpayer; Taxation e-System